FAKTOR PENGETAHUAN DAN KETERSEDIAAN DENGAN PENGGUNAAN KONDOM DALAM PENCEGAHAN HIV AIDS PADA WANITA PEKERJA SEKS - Celine Delvi Natasya; Shinta Kristianti; Eny Sendra (Jurnal Ilmu Kebidanan, 2023)
Human Immunodeficiency Virus (HIV) infection is a spectrum of diseases that attack immune cells which includes primary infection, with or without acute syndrome, asymptomatic stage, to advanced stage. According to the risk group, FSW (Women Sex Worker) occupies a high risk group for HIV transmission. FSW knowledge about the benefits of condoms is one of the factors in using condoms, out of 77 FSWs, 41 (53.4%) have poor knowledge. Of the 33 FSWs who did not provide condoms, 15 (20.5%) used condoms and 18 (24.7%) did not. The general objective of this study was to explaining the relationship between knowledge and availability of condoms with condom use in an effort to prevent the transmission of HIV/AIDS in female sex workers based on a literature study.. This literature review research was used a systematic mapping study design with literature sources obtained from the Pubmed database, and Google Scholar. The literature collected by using PEOS was then selected to produce 10 articles that were screened and analyzed using the presentation of the results of a literature review. Based on the 10 articles analyzed, it produced a good knowledge factor that made FSW consistently use condoms during sexual intercourse. The factor of the availability of condoms in the localization makes it easier for FSWs to always use condoms in every sexual transaction with customers. There is a relationship between knowledge factors and condom availability factors with condom use in an effort to prevent HIV/AIDS transmission in FSW.